A modernização do ginásio e a manutenção da ordem - Nunes, Zilda Clarice Rosa Martins (1979)
This dissertatlon aims at presenting a historical re - constitution of the process of rnodernization of the Brazilian secondary school system, which reached its climax with the 'Reforma do Ensino do Primeiro Grau' in the 70 's and with the creation of a new fundamental school. Most of the propasals for the creation of a new secondary schpol, in the 50's and 60's, tried to meet the needs of the political and econornic models of that period. Between 61-64, a criticaI phase of the economic development medel, new projects of secondary education carre up, su.ch as the Communi ty and the Vocational Uigh-Schools. Tl)ese projects proposed a new peda gogical practlce I airning at making man conscious of hin5elf as a historical and productive being and, therefore, oriented towards a transformation of society. The national educational policy, after 1964, rejected . the proposals for a more conscience-building secondary education and presented the Comprehensive High-Schools as a strategy for the nation-wide re formulation of the secondary s chool. It was concluded that the projects for the renovation of the secondary school arose out of the contradictions of the economic development mode!. While the Comprehensive HighSchools presented a pedagogical proposal compatible with the upkeep of the peri ferie capi talism, the projects for the creation of the Community and Vocational High-Schools o f fered a different answer to the cultural dornination policy.